Предмет: Математика, автор: 8883695

Помогите пожалуйста!!!!!​

Приложения:

Ответы

Автор ответа: smoljanov13
1

Пошаговое объяснение:

5\frac{5}{11} - 4\frac{9}{11} = \frac{60}{11}  - \frac{53}{11} = \frac{7}{11} \\13\frac{8}{9} - 11\frac{4}{9} = \frac{125}{9} -\frac{103}{9} =\frac{22}{9} =2\frac{4}{9} \\6\frac{5}{7} -4\frac{6}{7} =\frac{47}{7} -\frac{48}{7} = -\frac{1}{7\\} \\25\frac{2}{9} -4\frac{8}{9} =\frac{227}{9} -\frac{44}{9} =\frac{183}{9} = 20\frac{1}{3\\} \\17\frac{12}{15} -8\frac{3}{15} = \frac{267}{15} -\frac{123}{15} = \frac{144}{15} = 9,6\\11\frac{11}{13} -9\frac{12}{13} =\frac{154}{13} -\frac{129}{13} =\frac{25}{13}

Похожие вопросы
Предмет: Русский язык, автор: zhenya782
Предмет: Русский язык, автор: AlinaSergeevna